Pengaruh Utang Luar Negeri, Suku Bunga, dan Kurs terhadap Produk Domestik Bruto (Studi Kasus: Turki, Indonesia, dan Malaysia) - Curvanomic, Op; B1011131056, Muhammad Rachman Pratomo Rachman (Jurnal Pembangunan dan Pemerataan, 2019)
This study aims to estimate the effect of external debt, interest rates, and exchange rates on gross domestic product in Turkey, Indonesia and Malaysia. The selection of the three countries is because these countries are among the three largest debtor countries in the Organization of Islamic Cooperation (OIC) members. Secondary data were obtained from sesric in the period 2000-2015. The analysis technique used is the dynamic panel data regression method with the Generalized Method of Moment (GMM) model. The results of this study indicate that the external debt variable is positively related but not significant to the GDP variable. While the interest rate and exchange rate variables are each negatively related and not significant to the GDP variable. But found a long-term relationship between the variables GDP, external debt, interest rates, and exchange rates.Keywords: External Debt, Interest Rates, Exchange Rates, Gross Domestic Product, Organization of Islamic Cooperation, Generalized Method of Moment.  DAFTAR PUSTAKABabu, J. O., Kiprop, S., Kalio, A. M., & Gisore, M. (2014). External Debt and       Economic Growth in the East Africa Community. African Journal of Business       Management , 8 (21), 1011-1018.Ekananda, M. (2014). Ekonomi Internasional. Jakarta: Erlangga.Ekananda, M. (2014). Analisis Ekonometrika Data Panel Edisi 2. Jakarta: Mitra       Wacana Media.Fatmawati, R. Y. (2015). Analisis Pengaruh Perdagangan Internasional dan Utang       Luar Negeri terhadap Gross Domestic Product Indonesia (Periode 1990-       2010). Jurnal Ekonomi dan Studi Pembangunan , 7 (1), 55-62.Korkmaz, S. (2015). The Relationship Between External Debt and Economic       Growth In Turkey. Economics, Finance, and Banking , 1-9.Lee, S.-P., & Ng, Y.-L. (2015). Public Debt and Economic Growth in Malaysia.       Asian Economic and Finance Review , 5 (1), 119-126.Malik, S., Hayat, M. K., & Hayat, M. U. (2010). External Debt and Economic       Growth: Empirical Evidence from Pakistan. International Research Journal       of Finance and Economic (44), 88-97.Nabilah, D., & Setiawan. (2016). Pemodelan Pertumbuhan Ekonomi Indonesia        Menggunakan Data Panel Dinamis dengan Pendekatan Generalized Method       of Moment Arellano-Bond. Jurnal Sains dan Seni ITS, 5 (2), 205-210.Organisation of Islamic Cooperation. (t.thn.). Diambil kembali dari Statistical,       Economic and Social Research and Training Centre for Islamic Countries:       sesric.orgPermata, R.D. (2011). Faktor-faktor yang Mempengaruhi Pertumbuhan Ekonomi di Kawasan  ASEAN+6 (Skripsi), Institut Pertanian Bogor, Indonesia.Rahman, M. M., Bashar, M. A., & Dey, S. (2012). External Debt and Gross       Domestic Product in Bangladesh: A Co-Integration Analysis. Management       Research and Practice , 4 (4), 28-36.Sagir, S. (2009). Kapita Selekta: Ekonomi Indonesia. Jakarta: Kencana.Simi, A.B., Suhandak., & Hidayat,R.R. (2015). Pengaruh Utang Luar Negeri dan          Fluktiasi Nilai Tukar Rupiah terhadap Pertumbuhan Ekonomi Indonesia:       Studi Pada Bank Indonesia Tahun 2003-2013. Jurnal Administrasi Bisnis.             (28), 1-9.Tambunan, T. T. (2008). Pembangunan Ekonomi dan Pembangunan. Jakarta:       Rajawali Pers.Widarjono, A. (2007). Ekonometrika: Teori & Aplikasi untuk Ekonomi dan Bisnis       (Kedua ed.). YogyakartaYacoub, Y., & Adelia, R. (2011). Pengaruh Belanja Publik dan Pertumbuhan          Ekonomi Terhadap Tingkat Kemiskinan di Kalimantan Barat. Jurnal          Ekonomi Bisnis dan Kewirausahaan, 2 (1), 53-69.